2013
DOI: 10.1103/physrevc.88.054618
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quasifission characteristics and timescales in heavy element formation reactions

Abstract: Background: The formation of superheavy elements by fusion of two massive nuclei is severely inhibited by the competing quasifission process. Purpose: Through extensive mass-angle distribution measurements, we map out the systematic dependence of quasifission characteristics as a function of the identity of the colliding nuclei. Methods: The Australian National University's Heavy Ion Accelerator Facility and CUBE spectrometer have been used to measure mass-angle distributions for 42 reactions forming heavy ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
227
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 159 publications
(239 citation statements)
references
References 54 publications
11
227
1
Order By: Relevance
“…Although this approach has been widely used, it could have limitations due to the fact that quasifission is not a statistical decay but a dynamical process, and that fusion-fission could be asymmetric due to, e.g., late-chance fusion-fission at low excitation energies [28] as well as shell structure of pre-scission configurations [29]. Correlations between mass and scattering angle of the fragments have also been measured extensively [25,[30][31][32][33]. In particular, they can be used to disentangle fast quasi-fission processes (few zeptoseconds) to longer reaction mechanisms associated with contact times between the fragments exceeding 10 − 20 zs (i.e., long-time quasifission and fusion-fission).…”
Section: Introductionmentioning
confidence: 99%
“…Although this approach has been widely used, it could have limitations due to the fact that quasifission is not a statistical decay but a dynamical process, and that fusion-fission could be asymmetric due to, e.g., late-chance fusion-fission at low excitation energies [28] as well as shell structure of pre-scission configurations [29]. Correlations between mass and scattering angle of the fragments have also been measured extensively [25,[30][31][32][33]. In particular, they can be used to disentangle fast quasi-fission processes (few zeptoseconds) to longer reaction mechanisms associated with contact times between the fragments exceeding 10 − 20 zs (i.e., long-time quasifission and fusion-fission).…”
Section: Introductionmentioning
confidence: 99%
“…Quasifission mass-angle distributions (MAD) first measured at GSI in the 1980s [2,5] showed that quasifission timescales could often be shorter than the rotation time of ∼10 −20 s. However, subsequently only a few measurements [6,7] were made until recent years, when an extensive series of experiments (using the Australian National University Heavy Ion Accelerator Facility and CUBE spectrometer) were carried out [3,[8][9][10][11][12][13][14][15][16]. The kinematic coincidence technique used in the measurements [2,3,17] provides direct information on the mass-ratio of the fragments at scission; thus, the data are represented in terms of mass ratio M R , rather than pre-or According to the characteristics of the MAD (minimum mass yield at symmetry, mass-angle correlation with peak yield at symmetry, and no significant mass-angle correlation), they are assigned as type MAD1, MAD2 and MAD3 respectively [3]. There is a clear correlation between the MAD class and the entrance channel charge product.…”
mentioning
confidence: 99%
“…Examples of MAD and deduced quasifission sticking time distributions are shown in Fig.1, for reactions forming the compound nucleus 234 Cm [3]. According to the characteristics of the MAD (minimum mass yield at symmetry, mass-angle correlation with peak yield at symmetry, and no significant mass-angle correlation), they are assigned as type MAD1, MAD2 and MAD3 respectively [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 provides target details and energy ranges for the reactions studied. Coincident fission fragments were detected in the CUBE detector, which consists of two large-area position-sensitive multi-wire proportional counters (MWPCs) [12]. A schematic view of the experimental setup is given in Figure 1.…”
Section: Methodsmentioning
confidence: 99%